The use of Pistia stratiotes compost as an ameliorant for chili growth and yields in the reclamation fresh tailing area of Timika, Papua - Prabawardani, Saraswati; Taberima, Sartji; Fatoni, Samsul; Mawikere, Nouke Lenda; Fenetiruma, Obadja Andris; Lyons, Graham (Journal of Degraded and Mining Lands Management, 2024)
Tailing land reclamation aims to improve the environment so that the tailing areas become productive for crop cultivation. The research was carried out in the tailings area of Mile 21.5 Timika from March to September 2022. The research aimed to study the dosage levels of Pistia stratiotes composts as an ameliorant to support the growth and yield of chili cultivated in the fresh tailings area. This study was laid out in a randomized block design with the Pistia stratiotes compost as a treatment, which consisted of PS1 = 1 kg/plant, PS2 = 2 kg/plant, PS3 = 3 kg/plant, and PS4 = 4 kg/plant in 6 replications. Based on the results, there was a significant effect of Pistia stratiotes compost on the growth and yields of chili. PS4 treatment produced the highest growth (plant height and leaf number) and highest yields (fruit number/plant, fruit weight/plant, fruit weight/plot, fruit weight/ha), while PS1 produced the lowest growth and yields. Chili produced 4.19 t/ha by PS4, indicating a high yield potential when tailings turned into a more stable growth media over time. There was a significant correlation between plant height and leaf number with the fruit weight. This shows that the vegetative growth component is closely related to increased chili yields. The high heritability value indicates the genetic factor influenced the growth and yields of chili more than the environmental factors. The metal contents in the chili fruit tissue are below the threshold level. The findings of this study emphasized the appropriate reclamation approaches using Pistia stratiotes compost as an ameliorant, which effectively improves the quality of tailing as growing media to maximize chili yields.